The Effectiveness of Permits for Opening State Land in the Land Bureaucracy Reform of Balikpapan City - Fadiya Muzahadah; Rasji Rasji (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2025)
Land is a strategic resource with significant social, economic, and political value, requiring fair management and legal certainty. The Balikpapan City Government has established Regional Regulation No. 1 of 2014 and Mayor Regulation No. 33 of 2017 concerning the Permit to Open State Land to regulate the control and utilization of state land by the public. This study aims to analyze the effectiveness of the Permit to Open State Land as an administrative instrument in supporting land bureaucracy reform and to identify obstacles that hinder its implementation. The research method employed is normative juridical, supported by empirical data obtained through document studies and interviews with officials from the Land and Spatial Planning Office and the Balikpapan City Land Office. The results indicate that, although the Permit to Open State Land normatively supports the principles of good governance, its implementation has not been fully optimal. Approximately 70% of applications were approved, while 30% were rejected due to overlapping land, incompatibility with spatial plans, and incomplete documentation. The main obstacles include the lack of integrated land data, weak post-issuance supervision, and limited institutional capacity. Therefore, strengthening digital systems, inter-agency coordination, and improving human resource competencies are key factors in enhancing the effectiveness and transparency of land governance.